Elevated levels of interleukin-9 in the serum of bullous pemphigoid: possible association with the pathogenicity of bullous pemphigoid - Koga, Hiroshi; Teye, Kwesi; Sugawara, Arisa; Tsutsumi, Masahiro; Ishii, Norito; Nakama, Takekuni (Frontiers in Immunology, 2023)
Bullous pemphigoid (BP) is an autoimmune subepidermal blistering disease (sAIBD). In addition to disease causing autoantibodies, several leukocyte subsets including, mast cells and eosinophils, play key roles in mediating skin inflammation. Detailed immunophenotyping and, more recently, the therapeutic effects of interleukin (IL)-4 receptor alpha inhibition in BP pointed to a prominent role of Th2 cells. Among other cell types, IL-9 is expressed by Th2 and mast cells and potentially drives allergic, Th2-dominated inflammation. Although cytokines in BP have been relatively well investigated, the role of IL-9 has remained enigmatic. This study aimed to evaluate the effect of IL-9 in BP. Serum IL-9 levels were significantly elevated in patients with BP and decreased upon induction of remission. Serum IL-9 levels were not elevated in epidermolysis bullosa acquisita, another sAIBD. The time-course analysis using serum sets from four patients with BP revealed that serum IL-9 was a sensitive biomarker of BP. IL-9-positive cells infiltrated dominantly in BP lesions, especially in the blister fluid, and Th9 cells were abundant. Therefore, IL-9 was elevated in the serum and lesions of BP, which could be a biomarker of BP.